2020
DOI: 10.21037/tau.2019.09.38
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral resection of bladder tumour (TURBT)

Abstract: The goals of transurethral resection of bladder tumour (TURBT) are to identify and eradicate visualized bladder tumour if technically safe and feasible and to obtain a specimen of satisfactory quality to enable accurate histological diagnosis. In the setting of high grade bladder tumour this generally entails the inclusion of detrusor muscle and assessment for the presence of associated carcinoma in situ (CIS), lymphovascular involvement or any variant form of bladder cancer. This will assist in determining ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 100 publications
0
43
0
Order By: Relevance
“…It is the fourth most common malignancy in men. 6 Primary diagnostic tool is cystoscopy and the most frequently used diagnostic procedure is TURBT. 7 In the present study 86% were neoplastic lesions and 14% were nonneoplastic lesions which were comparable with the study of Shruthi et al 7 and Shrestha et al 8 The commonest age group of tumor presentation was 60-80 years with a male to female ratio of 4.6:1 which were comparable with other studies Shrestha et al 8 and Kousthuba et al 9 The most common presenting complaints were hematuria followed by urgency, frequency, and pain abdomen which were comparable with a study conducted by Shruthi et al 7 The most common non-neoplastic lesion in our study is cystitis cystic (8%) followed by urothelial hyperplasia(4%).…”
Section: Discussionmentioning
confidence: 99%
“…It is the fourth most common malignancy in men. 6 Primary diagnostic tool is cystoscopy and the most frequently used diagnostic procedure is TURBT. 7 In the present study 86% were neoplastic lesions and 14% were nonneoplastic lesions which were comparable with the study of Shruthi et al 7 and Shrestha et al 8 The commonest age group of tumor presentation was 60-80 years with a male to female ratio of 4.6:1 which were comparable with other studies Shrestha et al 8 and Kousthuba et al 9 The most common presenting complaints were hematuria followed by urgency, frequency, and pain abdomen which were comparable with a study conducted by Shruthi et al 7 The most common non-neoplastic lesion in our study is cystitis cystic (8%) followed by urothelial hyperplasia(4%).…”
Section: Discussionmentioning
confidence: 99%
“…Though many European studies showed size and multiplicity increase risk of recurrence, our patients have late presentations which probably made the proportion of recurrence higher in this group. It needs further prospective studies to make a conclusion ( 9 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radical surgical resection is the main treatment for NMIBC, and most patients can be cured by transurethral resection of bladder tumor (TURBT) [ 5 ]. The application of anesthesia is an indispensable part of the operation, and the effects of different anesthesia methods are different, which directly relates to whether the operation can be carried out smoothly.…”
Section: Introductionmentioning
confidence: 99%